Precise in-situ characterization and cross-validation of the electromagnetic properties of a switched reluctance motor - Xiao Ling; Liang Gong; Bingchu Li; Chengling Liu (Artificial Intelligence in Agriculture, 2020)
The electrical-magnetic characteristics of a Switched Reluctance Motor (SRM) exhibit highly nonlinear relationship with respect to the rotor position and excitation current, which poses challenges for both precise static measurements and exact calculation of these properties in real-time control. To guarantee that an in-lab test result can be used in the application, firstly a measurement method is proposed to characterize the SRM's electromagnetic properties such as the flux linkage, magnetic co-energy, phase inductance and electromagnetic torque on the basis of an installed SRM control circuitry and half-bridge power converter. By this means the characterization process is equivalent to the online observation in its results. Secondly, a theoretical model is built to discriminate the physical meaning between the incremental inductance and the phase inductance, which is the origin of other relevant parameters. This helps to guide the correct utilization of the characterization result. Thirdly an in-situ cross-validation experimentation according to the magnetizing and demagnetizing status measurement verifies the feasibilities and accuracy of the proposed inductance measuring method, which avoid a dubious FEM-based comparison between the numerical calculation and experimental results. Cross-validation experiment shows that the proposed in-situ characterization scheme obtains an accurate full-range electromagnetic properties. The proposed methodology breaks the barrier between the in-lab measurement and on-line utilization of the SRM parameters, highlighting the merits that it completely includes the in-situ factors and replicates the operational scenario without the need of specifically designed instrumentation, which is especially suitable for rapid field characterization for high power motors.